A facile synthesis of triazine integrated antipyrine derivatives through ecofriendly approach. Issue 2 (17th January 2021) - Rammohan, Aluru; Reddy, Guda Mallikarjuna; Krinochkin, Alexey P.; Kopchuk, Dmitry S.; Savchuk, Maria I.; Shtaitz, Yaroslav K.; Zyryanov, Grigory V.; Rusinov, Vladimir L.; Chupakhin, Oleg N.
Abstract: The present study describes a facile and solvent free synthesis of 1, 2, 4-triazine antipyrine derivatives (2a–f ) in prominent yields (70–85%) over nucleophilic substitution of 5-carbonitrile triazines. Further, we strained to convert them into pyridine analogues (3a–f ) over aza -Diels-Alder reaction with norbornadiene as dienophile but it was an unsuccessful attempt. It is an assumption we made that the antipyrine substituent primes the triazine electronically unfavorable at 1, 2- aza position. All the synthesized compounds were confirmed by using 1 H NMR, 19 F NMR, 13 C NMR and Mass spectral studies. Furthermore, this stated synthetic approach is ecofriendly as there are no toxic intermediates and also, the antipyrine derivatives can be aiding as promising templates for the development of new pharmaceutical scaffolds. Graphical Abstract: